Being-for-itself and the Ontological Structure: Can Being-for-itself Avoid Bad Faith?. Issue 2 (1st December 2020) - Santoni, Ronald E.
Abstract: In this paper, I pay tribute to Jonathan Webber, one of the most dependable interpreters among recent Sartre scholars. I do so by challenging both him and Sartre on an issue that has long frustrated my work on Sartre. In short, Sartre contends that the For-itself's desire to be (and to pursue) Being-in-itself-for-itself (i.e., God) is in bad faith. This raises two issues: (1) Is this desire to be ens causa sui part of the ontological structure of the For-itself? (2) If so, is bad faith an essential part of the human being? I contend that the desire to be the In-itself-for-itself is, on Sartre's premises, part of the ontological structure of an existing human being ( pour-soi ). As our original flight from freedom and "fundamental project, " this constitutes bad faith's "coming into the world, " and remains part of Being-for-itself's "natural" disposition to bad faith.